Fatty liver disease in living liver donors: a single‐institute experience of 220 donors. (17th September 2021) - Fang, Wen; Noda, Momoko; Gotoh, Kunihito; Morooka, Yuki; Noda, Takehiro; Kobayashi, Shogo; Doki, Yuichiro; Eguchi, Hidetoshi; Umeshita, Koji
Summary: We retrospectively reviewed 220 living liver donors, with a focus on the development of postoperative fatty liver. Data regarding demographics, comorbidities, imaging tests, operations and biopsies were obtained from medical records. We used unenhanced CT and USG to diagnose fatty liver. Donor candidates with fatty liver underwent weight loss intervention until imaging tests no longer demonstrated any features of fatty liver. Among 220 donors, 61 were diagnosed with preoperative fatty liver. The mean BMI of these 61 donors significantly decreased from 24.9 at the first visit to 23.6 kg/m 2 immediately before surgery ( P = 0.0386). A multivariate analysis revealed the following significant risk factors for postoperative fatty liver: male sex ( P = 0.0033), BMI immediately before surgery ( P = 0.0028) and a history of treatment for preoperative fatty liver ( P = 0.0231). Postoperative fatty liver was often refractory to weight loss intervention. No improvement was observed in 14 of the 32 donors who had been diagnosed with fatty liver postoperatively, and one of the 14 donors even developed NASH. In conclusion, special attention should be paid to prevent fatty liver after surgery in male donors who show a high BMI immediately before surgery and with a history of treatment for preoperative fatty liver, and lifelong follow‐up is recommended. Abstract : Life‐long follow‐up of living liver donor is recommended, especially for donors with above‐mentioned risk factors.